2005
DOI: 10.1097/01.tp.0000186382.81130.ba
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy after Transplantation

Abstract: As newer immunosuppressive regimens have steadily reduced the incidence of acute rejection and have extended the life expectancy of allograft recipients, posttransplant malignancy has become an important cause of mortality. In fact, it is expected that cancer will surpass cardiovascular complications as the leading cause of death in transplant patients within the next 2 decades. An understanding of the underlying pathobiology and how to minimize cancer risks in transplant recipients are essential. The etiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
387
0
20

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(420 citation statements)
references
References 96 publications
13
387
0
20
Order By: Relevance
“…6 According to a validated lung cancer risk model, 10 the 10-year risk of developing lung cancer in a non-transplant recipient of our population's mean age (55.5 years) and smoking history (49.5 pack-years) is no more than 2% with continued tobacco exposure. In our study, the frequency was 6.9% over a mean follow-up time <10 years (5.5 years in SLTx patients), implying a much higher than expected incidence of lung malignancy in the SLTx population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…6 According to a validated lung cancer risk model, 10 the 10-year risk of developing lung cancer in a non-transplant recipient of our population's mean age (55.5 years) and smoking history (49.5 pack-years) is no more than 2% with continued tobacco exposure. In our study, the frequency was 6.9% over a mean follow-up time <10 years (5.5 years in SLTx patients), implying a much higher than expected incidence of lung malignancy in the SLTx population.…”
Section: Discussionmentioning
confidence: 90%
“…6 In addition, since the publication of some earlier reports, the mean age of lung transplant recipients has increased steadily along with a concurrent increase in chronic obstructive lung disease (COPD) as an indication for transplantation relative to other nontobacco-related diagnoses 7 ; thus, the risk of lung cancer in lung transplant recipients may be increasing secondarily to these trends in transplant demographics.…”
mentioning
confidence: 99%
“…1 One compelling piece of evidence includes the increasing risk of cancer in immunosuppressed patients after organ transplantation, and patients with inherited defects in immune function. 1,27 In addition, animal models have demonstrated that the immune system exerts both host protection and tumor-sculpting/'immunoediting' effects on developing tumors. 1 For instances, 3-methylcholanthrene-induced sarcomas established in immunodeficient SCID or RAG2 À/À mice are more immunogenic than sarcomas induced in fully immunocompetent congenic mice (for review see Dunn et al 1 ).…”
Section: Dcs In Tumor Immunosurveillancementioning
confidence: 99%
“…Long-term use of calcineurin inhibitors such as CsA in solid organ and BMT is associated with increased risk of cancer. [32][33][34] While immunosuppression appears to be the principal predisposing factor, others have argued that compounds such as CsA can also inhibit the repair of DNA damage. 33,[35][36][37] A precedent for the role of immunosuppressive agent-induced DNA damage likely impacting on cancer predisposition has recently been described regarding azathioprine.…”
Section: Discussionmentioning
confidence: 99%